A comparative study of the novel externally-attached precast SRC braced-frames for seismic retrofitting under near-field spectrum-compatible non-stationary stochastic earthquake. (April 2023) - Xu, Ji-Gang; Cao, Xu-Yang; Shi, Jianzhe; Wang, Zhun
Abstract: Seismic retrofitting is a hot issue in the field of earthquake engineering, and the externally-attached substructure approach is a well-known solution due to its no-disturbing construction and high-efficiency improvement. In this paper, a comparative study of a novel externally-attached precast steel-reinforced-concrete (SRC) braced-frames for seismic retrofitting is performed, and the near-field spectrum-compatible non-stationary stochastic earthquakes are generated as the excitation to reflect the input uncertainty. The construction and simulation approaches of the novel substructure are first introduced, and then the generation theories of near-field spectrum-compatible non-stationary stochastic earthquake are explained. The comparative study of five scenarios is conducted, via a 3-span-5-story existing reinforced concrete frame, and a series of performance indices are adopted for analysis, including the inter-story deformation, inter-story shear force, section-mechanical performance, and energy-consumption capacity. In general, the comparison study verifies the effectiveness of the novel externally-attached SRC braced-frames for retrofitting, and the external frame obviously reduces the axial force of the existing beams and columns, which indicates that the shear demand is transferred to the external substructures and the damage accumulation is well controlled after retrofitting. Although the inter-story performance and energy-dissipation capacity of the external substructures are not as direct as the bare brace scenarios, the external frames alleviate the potential premature damage of the existing joints and avoid the infills or facades of the existing building to place external braces, which provides a practical reference for the engineering application and future research.